2001
DOI: 10.1055/s-2001-14528
|View full text |Cite
|
Sign up to set email alerts
|

DNA Diagnosis and Management of Hermansky-Pudlak Syndrome in Pregnancy

Abstract: Hermansky-Pudlak syndrome (HPS) is an autosomal recessive disorder characterized by oculocutaneous albinism (OCA), platelet storage pool deficiency, and ceroid lipofuscin deposition. Sequelae including pulmonary fibrosis, colitis, and hemorrhagic diathesis can impact obstetric management. An 18-year-old primigravida with OCA was diagnosed during pregnancy with Hermansky-Pudlak syndrome by DNA analysis. Uneventful vaginal delivery occurred at term following prophylactic platelet transfusion. Women of northweste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Genetic testing may be performed during pregnancy. 3 Care for the obstetric patient with HPS is a multidisciplinary approach, involving obstetricians, hematologists, geneticists, anesthetists, and pulmonologists. It is difficult to state definitive guidelines due to the scarcity of case reports.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing may be performed during pregnancy. 3 Care for the obstetric patient with HPS is a multidisciplinary approach, involving obstetricians, hematologists, geneticists, anesthetists, and pulmonologists. It is difficult to state definitive guidelines due to the scarcity of case reports.…”
Section: Discussionmentioning
confidence: 99%
“…She was given five units of platelets prophylactically and spontaneously delivered a healthy male infant without complications. 8 Reiss et al 9 reported two cases of Puerto Rican women, one presenting at 40 weeks and the other at 39 weeks of gestation. One patient received prophylactic platelet transfusion while the other did not; both had uncomplicated deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…She was given five units of platelets prophylactically and spontaneously delivered a healthy male infant without complications. 8 Reiss et al…”
Section: Discussionmentioning
confidence: 99%
“…The data extracted from the cases are represented in Tables 1 and 2. 13,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In all the studies, diagnosis of HPS was confirmed by a hematologist; of which nine (56%) studies fully described the diagnostic criteria met by subject(s). Further subgroup analysis revealed a high percentage of studies (n = 15; 94%) adequately described and reported study outcome(s) and ensured adequate subject follow-up.…”
Section: Re Sultsmentioning
confidence: 99%
“…22 Pregnancies managed with hemostatic platelet transfusion had lower EBL (8 cases, highest EBL 800 ml) compared to those managed with desmopressin (9 cases, highest EBL 1600 ml). 13,[16][17][18][19][20][21][22][23][24][25][26][27] Major PPH occurred in 3/9 (33%) cases in the desmopressin group compared to none when platelets were used. Platelets and packed red cells transfusion were required to treat PPH in 4/9 (44%) and 2/9 (22%) cases in the desmopressin group respectively.…”
Section: Postpartum Hemorrhagementioning
confidence: 99%